Trauma and donation after circulatory death: a case series from a major trauma center. Issue 3 (March 2021) - Circelli, Alessandro; Brogi, Etrusca; Gamberini, Emiliano; Russo, Emanuele; Benni, Marco; Scognamiglio, Giovanni; Nanni, Andrea; Coccolini, Federico; Forfori, Francesco; Fugazzola, Paola; Ansaloni, Luca; Solli, Piergiorgio; et al.
Even with encouraging recipient outcomes, transplantation using donation after circulatory death (DCD) is still limited. A major barrier to this type of transplantation is the consequences of warm ischemia on graft survival; however, preservation techniques may reduce the consequences of cardiac arrest and provide better organ conservation. Furthermore, DCD in trauma patients could further expand organ donation. We present five cases in which organs were retrieved and transplanted successfully using normothermic regional perfusion (NRP) in trauma patients. Prompt critical care support and surgical treatment allowed us to overcome the acute phase. Unfortunately, owing to the severity of their injuries, all of the donors died. However, the advanced and continuous organ-specific supportive treatment allowed the maintenance of general clinical stability and organ preservation. Consequently, it was possible to retrieve and transplant the donors' organs. Death was ascertained in accordance with cardio-circulatory criteria, which was followed by NRP. We consider that DCD in trauma patients may represent an important source of organs.